Advances in Psychology and Law Volume 3 (Advances in Psychology and Law,, 2018)
The latest entry in this noteworthy series continues its focus on psychological issues relating to legal and judicial matters, with sound recommendations for situational and system-wide improvement. Salient concerns are described both in areas where their existence is frequently acknowledged (juror impartiality, the juvenile justice system) and where they are rarely considered (Miranda warnings, forensic mental health experts). Authors describe differences between professional and lay concepts of justice principles--and the resulting disconnect between community sentiment and the law. Throughout these chapters, psychological nuances and their legal implications are made clear as they relate to lawyers, jurors, suspects, and victims. Included among the topics: · From the headlines to the jury room: an examination of the impact of pretrial publicity on jurors and juries. · Victim impact statements in capital sentencing: 25 years post-Payne. · Psychology and the Fourth Amendment. · Examining the presenting characteristics, short-term effects, and long-term outcomes associated with system-involved youths. · Indigenous youth crime: an international perspective. · An empirical analysis of law-psychology journals: who's publishing and on what? As with the others in the series, this third volume of Advances in Psychology and Law will interest researchers in legal psychology and related disciplines (e.g., criminal justice) as well as practicing attorneys, trial consultants, and clinical psychologists. .